Analisis Faktor-Faktor Yang Berhubungan Dengan Usia Menopause Di Puskesmas Mekar Kota Kendari - Kartini (Health Information : Jurnal Penelitian, 2020)
Menopause is one of the stages of life that will surely be experienced by all women. The age at which menopause occurs in women varies. The purpose of this study was to determine factors related to the age of menopause at the Mekar Health Center in Kendari City. The research design used is Cross Sectional. The sample in this study was menopausal women in Kendari City. Data types are primary and secondary data. Data obtained from interviews with menopausal women in Kendari City. Data were analyzed by Chi square test (?2). The results of the study stated that most of the age of menopause in women in the normal category (ages 45-55 years). There is a relationship between parity and menopausal age (?2 = 12.19; p = 0.002); a relationship between the age of menarche and the age of menopause (?2 = 13.86; p = 0.001); a relationship between the age of first giving birth and the age of menopause (?2 = 6.24; p = 0.012); a relationship between the history of oral contraceptive use and the age of menopause (?2 = 7.456; p = 0.024); a relationship between physical activity and menopausal age (?2 = 10.77; p = 0.005); no relationship between smoking history and menopausal age in women (?2 = 0.276; p = 0.599). Women of childbearing age are expected to increase information about menopause and factors related to menopausal ageas to reduce anxiety in entering menopause.